IN VITRO SCREENING FOR ANTAGONISTIC POTENTIAL OF TRICHODERMA SPECIES AND FLUORESCENT PSEUDOMONAS AGAINST FUSARIUM SOLANI FOR MANAGEMENT OF SOYBEAN WILT - MANOJ KUMAR SAHU; PUSHPANJALI WAGH; GIRIJA SHANKAR; INDRA KUMAR; K. P. VERMA; A. S. KOTASTHANE (The Bioscan, 2015)
Soybean wilt disease caused by Fusarium solani f. sp. glycine is one of the most important diseases of soybean. In vitro evaluation among three isolates of Trichoderma and twenty four isolates of fluorescent Pseudomonas against ten and one aggressive isolates of F. solani respectively. The maximum mycelial growth inhibition of test pathogen was observed 13.66 mm (84.40%) with T. harzianum 2 in SF2 followed by 15.33 mm (82.37%) with T. harzianum 1 in SF8 isolate. All the isolates were effective in inhibiting the mycelial growth (65.15 - 84.40 %) over control. Among all the isolates of fluorescent Pseudomonas significantly superior in reducing the mycelial growth over control except P141 and P179, whereas highest mycelial growth inhibition 35.66 mm (59.13%) was observed in P85 followed by 45 mm (48.46%) in P167 isolate. These antagonist isolates inhibited 6.85 to 59.13 per cent mycelial growth of test fungus.